Oportunidades y amenazas para la Argentina de un acuerdo Mercosur - Unión Europea: Un estudio de impacto sectorial - CEI - Centro de Economía Internacional (Buenos Aires) (Centro de Economía Internacional (CEI), 2003)
– Trade relations with the European Union are of critical importance to our country. Historically, and aside from economic cycles and trade agreements that may have geographically redirected trade flows, the Old World is one of Argentina's main trade partners, both in terms of the origin of our imports as well as in terms of the destination of our sales, which points to the high degree of complementarity existing between the production structures of both regions. To this should be added other political factors -such as the importance of the European bloc in the international scenario- and economic factors -such as the possible effect on other negotiation forum, such as FTAA or WTO- , which enhance even more the importance of a free trade agreement between Mercosur and the European Union. The concessions granted in a free trade agreement between two blocs may modify exchanges between the partners. On the one hand, obtaining tariff preferences tends to lead to an increase in exports towards the new partner; on the other hand, this may involve the loss of preferential access exclusivity for the older partners (in this case Mercosur partners), which means that sales to that destination face new competition which may partially or totally displace exports. This is what creates opportunities and threats for foreign trade, through changes in exports and imports, which in theoretical terms causes trade creation and trade diversion effects.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Argentinien; EU-Staaten